The Passion of the Digital: the Ontology of the Photographic Image in the Age of New Media - Basu, Anustup (Recherches sémiotiques / Semiotic Inquiry, 2011)
Using Mel Gibson’s 2004 film and cultural phenomenon The Passion of the Christ as a launching pad, this essay meditates on some questions about the twentieth century legacy of competing realisms, the graphic imperative of contemporary digital image cultures, and the ontological conundrums involving technology and mass media. Passion is an onto-theological filmic ‘event’ that derives equally from an almighty religiosity as well as a cultish process of being enraptured by certain ritual values of a new-age technologism of sound and image. This endographic writing out of the Gospel narrative at the level of the tissue and nerve of the committed viewer affirms a transcendental truth already there in an internal cosmos of belief instead of working in terms of an externally navigable ‘realist’ representation of the world that seeks to ‘bear away our faith’. This is rendered possible when unquestioning belief in Christ and in his momentous sacrifice is met by an embracing of technology without the skepticism of a scientific temper.